2017
DOI: 10.1038/s41409-017-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor in poor mobilizers with non-Hodgkin’s lymphoma: a multi-center time-motion analysis

Abstract: High-dose chemotherapy alongside peripheral blood stem cell (PBSC) infusion has become the standard of care in different hematologic malignancies. The goal of PBSC mobilization is to allow collection of sufficient CD34+ cells to proceed to transplantation. The current mobilization regimen with granulocyte colony-stimulating factor (G-CSF), alone or in combination with chemotherapy, still fails in 10-25% of patients. Plerixafor is able to rescue most of these patients from mobilization failure. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…The CI of the difference is based on the Wald asymptotic CI with continuity correction method. In adults, plerixafor has been observed to be advantageous in patients considered to be poor mobilizers using the current consensus threshold for poor mobilization in adults (<20 CD34+ cells/µL) [5][6][7]. However, the adult "consensus" threshold for poor mobilization may not be appropriate in the pediatric setting [8].…”
Section: Discussionmentioning
confidence: 99%
“…The CI of the difference is based on the Wald asymptotic CI with continuity correction method. In adults, plerixafor has been observed to be advantageous in patients considered to be poor mobilizers using the current consensus threshold for poor mobilization in adults (<20 CD34+ cells/µL) [5][6][7]. However, the adult "consensus" threshold for poor mobilization may not be appropriate in the pediatric setting [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the advantages of LIPEG use in the mobilization setting compared with FIL, despite similar total apheresis yields, include a single administration and lower laboratory costs as a consequence of fewer apheresis sessions that obviously compensates the lower costs of biosimilar filgrastim (Table ). In addition, plerixafor, which may also reduce the time spent on apheresis, was needed in only 13% of the patients in the LIPEG group. Further, early hematologic recovery appeared to be faster in the LIPEG group, and there was also a trend for a shorter hospitalization period during auto‐SCT compared with the other groups, making this G‐CSF appealing in the mobilization of CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Average leucapheresis per person of 2.64 was achieved in PY group after adding plerixafor which was comparable to 2.47 in the PN group. A multi centre time motion analysis of plerixafor in poor mobilizers of non Hodgkins lymphoma patients showed that poor mobilizers who received plerixafor had a decrease in apheresis sessions and thereby costs [14]. Median value of apheresis CD34 count on day 1 was 1.75 in PY group and 2.63 in the PN group.…”
Section: Discussionmentioning
confidence: 99%